Effects of Yoga training on Personality of school students - Semwal, Jayanti; Juyal, Ruchi; Kishore, Surekha; Kandpal, S D (Indian Journal of Community Health, 2014)
Background: Personality is not only the physical and mental aspect but also the behaviour or adjustment to the surroundings of an individual. It develops gradually from the childhood –adulthood & may affect or gets influenced by various factors like genetic, social and environmental. Adolescent period is the best time to shape & determine ones destiny. We can channelize their energy in a right direction to make them a responsible human being. Yoga is one intervention mentioned by Pallant (2000), as being directed at increasing control over one’s physical reactions. Method: A longitudinal interventional study was done in school children of classes VIII- X. Introversion – Extroversion Inventory was used to assess the type of personality before & after yoga therapy and appropriate suggestions were given accordingly. Results: A total of 271 secondary school students were included in the study. Before intervention majorities (77.1%) were of ambivert trait, Girls were found to be more introvert & boys were more extroverts. After yoga therapy pattern was same but the number of students decreased in introvert & extrovert personality from (10.7 & 11.5) to (2.9 & 4.8) respectively. Conclusion: The present study has shown that training in yoga helped in modifying the personality type in adolescent students. After home, school is the second important place, which help in developing sense of morality and sociability .Yoga is cost effective and easy to implement but need to be regularly reinforce to bring about a sustainable behavioural change.